(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
The study aimed at identifying the plants of Bousaada district of M’sila province, South East Algeria, used by the local people as traditional medicines and analyzing their use value. The ethnomedicinal use information was collected by interviewing local informants using structured questionnaires through regular field surveys. A total of 193 species belonging to 69 families was identified. Lamiaceae and Asteraceae were the most commonly reported medicinal plants with 85 and 71 species, respectively. Artemisia herba-alba and Juniperus oxycedrus were the most widely used plants as the traditional medicine by the local population. The highest use value (UV) was observed for Citrus lemon (L.) Burm., Ficus carica L., Moringa oleifera Lam. and Olea europaea L. (UV=5). The highest fidelity level (FL) value was for 73 species. The calculated informant consensus factor (ICF) showed that diseases related to gastrointestinal disorders and diseases of the glands attached to the digestive system diseases present the highest values. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 61-78